A assistência jurídica gratuita como instrumento de concretização do acesso à justiça: uma análise das políticas públicas desenvolvidas pelo Estado da Bahia no Município de Ipiaú - VIEIRA, Luan Maia (2017)
The central objective of this research is to analyze the public policies developed by the State of Bahia with the purpose of promoting the full, effective and universal fundamental right to access to justice through free legal assistance in the municipality of Ipiaú/BA, expected in the Multiannual Plan (PPA) 2012-2015 and 2016-2019. Despite the express constitutional determination of the State's obligation to provide free legal assistance to those in need, the institution responsible for providing this assistance isn’t present in all municipalities in Brazil, especially in small municipalities that represent a large portion of the country. Then, the problem of this research consists of the following question: How does the guarantee of the fundamental right to access to justice by the State of Bahia to the needy population of the municipality of Ipiaú, through the public policies foreseen in the Multiannual Plan 2012-2015 and 2016-2019? From the methodological point of view, using the hypothetical-deductive approach, was chosen quantitative-qualitative research, using descriptive-exploratory research. Still in relation to the methodological procedure, the documentary analysis and the application of questionnaires and interviews were used as data collection technique. In the end, it was verified that, due to the fact that the public policy to promote access to integral and free justice in the municipality of Ipiaú/BA - due to the lack of a Public Defender’s office unit in place, there isn’t active defender in the city, the population can’t to be attended in another city and because the municipality wasn’t contemplated by the itinerant projects -, it was concluded by confirming the preliminary hypothesis of the research: the population in need of the municipality of Ipiaú is excluded from the possibility of questioning / claiming their rights before the power judiciary, being marginalized from the fundamental right of access to justice and other rights derived from it. Thus, recommendations and suggestions for the improvement of public policy and its management were evidenced.